Analisis Fenomena Mental Health Pada Kasus Bullying di Kalangan Gen Z Sebagai Permasalahan Sosial dalam Perspektif Antropologi Hukum - Efriana, Tiara Okta; Lubis, Nurrinda Lestari; Triananda, Melinda; Afandi, Muhammad; Suherman, Asep (PPSDP Undergraduate Journal of Educational Sciences, 2024)
The development of the times has changed the composition of the population with a decrease in the number of baby boomers and an increase in generations X and Y. Generation Z, which is starting to enter the workforce, attracts attention with unique characteristics such as better multitasking capabilities and dependence on digital technology. This research shows that the Z generation has great ambitions, is practical, and values freedom, and has an interest in detail and a desire to acknowledge their achievements. In research, the World Health Organization (WHO) defines mental health as a state of well-being that allows individuals to develop their potential and overcome the stresses of everyday life. Mental health screening is designed to identify children and adolescents who may be at risk of developing mental health disorders, with the aim of identifying problems and determining the necessary interventions. Bullying, a form of physical and psychological violence, is also a concern in the context of mental health, especially in generation Z. The phenomenon of bullying can cause negative impacts such as loss of self-confidence, stress, trauma, and revenge. The results of the research show that it is important for educational institutions such as schools or those responsible for the implementation of education to protect students from intimidation and violence.